2020
DOI: 10.1002/path.5405
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in development and disease: conservation to mechanisms

Abstract: Our genomes contain the blueprint of what makes us human and many indications as to why we develop disease. Until the last 10 years, most studies had focussed on protein-coding genes, more specifically DNA sequences coding for proteins. However, this represents less than 5% of our genomes. The other 95% is referred to as the 'dark matter' of our genomes, our understanding of which is extremely limited. Part of this 'dark matter' includes regions that give rise to RNAs that do not code for proteins. A subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 108 publications
0
118
0
1
Order By: Relevance
“…LncRNAs can be divided into two functional groups based on their sub-cellular localization: (1) nuclear and (2) cytoplasmic. Nuclear lncRNAs can influence gene expression via various mechanisms, including chromatin remodeling, protein sequestration and the enhancement or dampening of promoter activity [ 107 ]. One of the ways that cytoplasmic lncRNAs can influence gene expression is by regulating the availability and stability of miRs by acting as miR “sponges” [ 107 ].…”
Section: Lncrnas and Hhtmentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNAs can be divided into two functional groups based on their sub-cellular localization: (1) nuclear and (2) cytoplasmic. Nuclear lncRNAs can influence gene expression via various mechanisms, including chromatin remodeling, protein sequestration and the enhancement or dampening of promoter activity [ 107 ]. One of the ways that cytoplasmic lncRNAs can influence gene expression is by regulating the availability and stability of miRs by acting as miR “sponges” [ 107 ].…”
Section: Lncrnas and Hhtmentioning
confidence: 99%
“…Nuclear lncRNAs can influence gene expression via various mechanisms, including chromatin remodeling, protein sequestration and the enhancement or dampening of promoter activity [ 107 ]. One of the ways that cytoplasmic lncRNAs can influence gene expression is by regulating the availability and stability of miRs by acting as miR “sponges” [ 107 ]. Although lncRNA mechanisms have been well characterized, evidence suggests that most lncRNAs are non-functional [ 107 ].…”
Section: Lncrnas and Hhtmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological function and molecular mechanisms of lncRNA in many kinds of human diseases in particular are constantly revealed [20,21]. Besides diseases, the role of lncRNA in development also has been reported [22]. LncRNAs have been reported that not expressed at each certain stages in development.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are >200nt and thought to lack the potential to encode proteins. LncRNAs are well known to play key roles in development and differentiation via several mechanisms (Dimartino et al, 2018;Tsagakis et al, 2020), such as the base-pairing of lnc-31 with Rock1 mRNA, to promote its translation during myoblast differentiation (Dimartino et al, 2018). ~40% of human lncRNAs are specifically expressed in the brain (Derrien et al, 2012), where they display precise spatiotemporal expression profiles (Ponting et al, 2009).…”
Section: Introductionmentioning
confidence: 99%